Kemandirian Wirausaha Narapidana pada Program Pembinaan Berbasis Kemitraan di Lapas Kelas III A Rangkasbitung - Fachriza Shiddiq Gunawan; Moh. Fikri Tanzil Muttaqin; Ahmad Fauzi; Yosi Asri Bandrio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the entrepreneurial independence of inmates through partnership-based development programs at Class III Rangkasbitung Correctional Institution. Work development programs serve as a form of social rehabilitation intended to improve inmates’ skills, productivity, and economic readiness after release from correctional institutions. This study employed a descriptive qualitative approach involving inmates actively participating in cooperative management, tailoring, barber services, handicrafts, and guitar-making activities. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed using thematic analysis to identify major themes related to skill development and entrepreneurial independence among inmates. The findings revealed that partnership-based development programs positively contributed to improving technical skills, responsibility, work discipline, and participants’ self-confidence. Furthermore, the programs helped inmates understand business opportunities and prepare for economic independence after completing their sentences. Partnership-based development programs also functioned as a form of social rehabilitation that supports inmates’ reintegration into society.